Prevalence of anxiety disorders among people living with HIV (PLWHIV) and experiencing neuropathic pain who attend clinics in Nkomazi Sub-District - Ochan, Walter O (Department of Public Health and Family Medicine, 2019)
Background: Clinical and research experience indicates that a high HIV prevalence setting will have a high occurrence of conditions that are associated with HIV. These conditions are not always infectious in nature. General physiological pain, neuropathic pain (NeuP) and anxiety disorders are conditions that have a high prevalence in people living with HIV (PLWHIV). There is, however, a literature gap on the prevalence of these conditions in Nkomazi Sub-district in South Africa’s Mpumalanga Province. This study therefore aimed to serve as a baseline study for the determination of the prevalence of anxiety disorders and neuropathic pain amongst PLWHIV who attended Highly Active Antiretroviral Therapy (HAART) clinics in Nkomazi Sub-district. Aim of the study: To determine the prevalence of anxiety disorders among PLWHIV with neuropathic pain who attended HAART clinics in Nkomazi sub-district. Objectives of the study: 1) To determine the prevalence of Neuropathic Pain among patients attending HIV clinics in Nkomazi Health District; 2) To determine the prevalence of Anxiety disorders among PLWHIV experiencing neuropathic pain who attended HIV clinics in Nkomazi sub-district. 3) To determine the Types of Anxiety Disorder among Nkomazi PLWHIV with NeuP who have one, or more anxiety disorders. Methods: The objectives were achieved through a cross-sectional study using an interviewer administered questionnaire. Three out of 34 facilities were sampled for the study and participants were recruited and interviewed for a month in April 2013. A total of 508 participants were recruited. The questionnaire was adapted from the Structured Clinical Interview DSM IV Axis I Disorders (Clinicians’ Version) or SCID-CV and the DN4 interview tool for neuropathic pain. The questionnaire also sourced demographic data from all participants. Age is summarised using non-parametric statistics. Categorical variables are summarised using percentages and a bar graph. The Chi-squared and the Fisher’s exact tests are used to compare binary categorical variables. The Prevalence Ratio is the relative measure of association used. The p-value is set at ≤0.05 for statistical significance. The 95% confidence interval (95 =% CI) depicts the precision of estimates. Ethical and access approval were granted by the University of Cape Town Research Ethics Committee and the Mpumalanga Department of Health respectively. Results: Participants were recruited at kaMhlushwa clinic (n = 203 or 39.96%; 95% CI: 35.67 – 44.37), Naas clinic (n = 126 or 24.80%) and Mangweni clinic. There were more females (77.56%; 95% CI: 73.68 – 81.12; n = 394) than males (22.44%; 95% CI: 18.88 – 26.32; n = 114). Pain prevalence was 46.06%; 95% CI: 41.66 – 50.51 (n = 234). The prevalence of neuropathic pain was 17.72%; 95% CI: 14.49 – 21.32 (n = 90) and that of anxiety disorders among those participants with Neuropathic pain was 80%; 95% CI: 70.25 – 87.69 (n = 72). Conclusion: This study confirmed the high prevalence of a complex disease burden in a high HIV prevalent Primary Care setting. The community has high prevalence of pain, anxiety disorders and neuropathic pain amongst PLWHIV patients on HAART.